Os sentidos argumetativos de trabalho em textos oficiais e em textos de estudantes do ensino médio - Euzébio, Gilmar de Assis (2015)
In the year 2011, started the implementation, in the majority of the state public schools of Rio Grande do Sul, the Polytechnic High School. The intention of the programme was, mainly, to perform the linking between the theory and practice at the students formation, from the discussions about the employment world. In this context, teachers were prepared to act in front of this new challenge, receiving materials about the work world as main theoretical support, which were produce by significant researches in the area. Among these materials, is the article Work as educational principle of the Real Pedagogic Practice, official document analyzed in this study. The theme of this dissertation establishes as being: the argumentative meanings of work in the educational context, in which the investigated problem is how the argumentative meanings of work expressed by students related with the expressed meanings in official texts of their school? As a result, the objective establishes as being: collating the conception of work in texts produced by young students of two schools, who participated in that experience, with the conceptions of work verified at the official text analyzed. The argumentative semantic establishes as theoretical mark of this dissertation, because presents us the opportunity of have a linguistic look about the argumentation which guides these texts about this question of work. Developed by Oswald Ducrot and Anscombre (1983) and expanded by Marion Carel (1992), the theory has as its basis the analysis of the argumentative chains that create meanings on the text. The argumentative meanings of work expressed in the student s texts differentiated itself from the meanings expressed by the common sense. The analysis showed that there is a conformity in the productions of the students with the indications presented by society that the work leads to success, because the social organization offers conditions to all the subjects that are willing to participate of the social life and to achieve the personal success through work